RADIOLOGY REQUEST FORMS (RRF) INADEQUATELY COMPLETED; THE CASE OF A TERTIARY HEALTH CENTER IN NORTHWEST NIGERIA - M, Danfulani; MA, Musa (International Journal of Clinical and Biomedical Research, 2015)
Background: The need and importance of adequately completing radiology request forms cannot be over emphasized. Thus, this study investigated the pattern in which radiology request forms are completed by clinicians in a tertiary health center. Methods: A total of two hundred and fourteen (214) samples of request forms were randomly selected from records of the Radiology Department of the Federal Medical Center, BirninKebbi, Nigeria. The request forms comprises of requests from various departments within the hospital. All the data collected from the request forms where entered into Microsoft excel and items/fields on the form were examined. Results: From this study, it was observed that out of the total 214 forms collected, 209 (97.7%) of the forms were not adequately completed with only 5 (2.3%) fully completed. Other items on the request form that were also least completed were the referring physicians name (2.3%), patient's full address (2.3%) and patients age (62.6%).Conclusion: We conclude that radiology request forms are inadequately completed as seen from the present study, thus the need to enlighten the referring physicians on the need to adequately and properly complete radiology request forms as this is vital in improving the accuracy of radiologists report / interpretation. KEYWORDS: Radiology; Physician; Request forms; Patients; Health center.